Technology-based Biliteracy Centers for the 21st Century Learner (GIST – Education and Learning Research Journal, 2014)
The purpose of this reflective article is to present an alternative that incorporates the four language skills in all content areas through technology-based duallanguage centers for emergent bilinguals at the elementary level. The authors propose a matrix to plan the centers and include three examples to facilitate language transfer in English and Spanish to foster biliteracy. The planning of the three projects is discussed as well as results from their implementation with elementary grade learners.
Keywords: Language transfer; technology; literacy centers; biliteracy; content development; digital literacy.